Geotechnical and Morphological Properties of Kuantan Bauxite - Muzamir, Hasan (2016)
Clients will be aware that bauxite is classed as a Group C cargo in the International Maritime Solid Bulk Cargoes (IMSBC) Code i.e. neither liable to liquefy (Group A) nor to possess chemical hazards (Group B). Bauxite is described as ‘a brownish, yellow claylike and earthy mineral, insoluble in water.’